(untitled) (Jurnal Agribisnis dan Agrowisata, 2026)
Analysis of factors influencing the income of rice farmers in Subak Munggu Tegallantang, Badung Regency. Subak Munggu Tegallantang is one of the subaks located in Badung Regency. Rice is the main commodity grown in this region. This research aims to analyze the cost structure of rice farming in Subak Munggu Tegallantang, determine the income of rice farming in Subak Munggu Tegallantang, and examine the factors that influence rice farming income in Subak Munggu Tegallantang. This research was conducted for four months in Subak Munggu Tegallantang, data collection methods included interviews and documentation, which were analyzed using quantitative and qualitative descriptive with the help of the SPSS 27 program. The results of this research show that the cost structure of rice farming in Subak Munggu Tegallantang consists of fixed costs with an average -an average of IDR 222,642.42 and variable costs with an average of IDR 2,626,122.73 with total costs of IDR 2,848,765.15. The average income of farmers in Subak Munggu Tegallantang is IDR 16,516,537.88. And from hypothesis testing using the t test, it is known that farming costs (X1) do not have a significant effect on farmer income, while land area (X2) and selling price (X3) have a significant effect on rice farmer income in Subak Munggu Tegallantang.